Analisis Miskonsepsi Siswa Kelas X pada Materi Gerak - Ovilia Putri Utami Gumay (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2021)
This research is motivated by problems that researchers obtained through library that research on physics misconceptions especially on a straight motion kinematics matter much done both domestically and abroad, but these studies have not been done in SMA Negeri Terawas environment. One of the problems misconceptions related to the problem students in the class X SMA Negeri Terawas is the low learning outcomes of students on the subject of motion kinematics straight. The purpose of this study was to determine the form of misconceptions experienced by X grade students, the low learning outcomes, especially on the subject of motion kinematics straight. This research is a descriptive method. Data collection techniques using multiple choice tests are the reasons, and the level of confidence (CRI). The subjects were taken through purposive sampling technique. From the analysis of students' responses, it was found that of the 14 items were presented, there are 7 items that indicate the occurrence miskonsepsi on students, 2 items showed lack of students to understand the concept, and 5 items showed a good mastery of concepts by students. Number of students who have reached 100 % for the misconceptions about the number 13 with an average high CRI is 4.74, and about the number 14 with an average of 4.76 CRI. The misconception occurs in sub subject matter motion free fall .